(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, the (2+1)-D quantum Zakharov-Kuznetsov (QZK) equation that describes how nonlinear ion-acoustic waves diffuse in magnetized plasma is studied. Firstly, The governing equation was transformed into a number of ordinary differential equations using symmetry analysis. After that, We used Kudryashov-Auxaliry Method (KAM) to develop a new kind of accurate answers for the QZK equation. The discovered solutions included a number of arbitrary constants that improved their dynamic characteristics. The resulting solutions represent solitary wave, single wave, and multisolitons solutions and include hyperbolic and trigonometric functions.